Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate, sodium-ion battery and power-related equipment

By adopting the Mn and B element coating design in the positive electrode material of sodium ion battery, the problems of reduced Na+ transmission and increased impedance of sodium ion battery at high voltage are solved, and the electrochemical performance and cycle life of the battery are significantly improved.

CN119230798APending Publication Date: 2024-12-31深圳为方能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636599.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When the existing sodium ion battery positive electrode materials increase the operating voltage, the Na+ transmission is reduced and the battery impedance increases.

Method used

The sodium ion battery positive electrode material adopts core and shell structure, where the shell contains Mn and B elements, which are mixed with the core material by calcining manganese and boron sources to form a cladding layer to improve interface stability, prevent chemical erosion of electrolytes and dissolution of transition metals .

Benefits of technology

Effectively maintain the stability of the electrode structure, reduce irreversible capacity loss, and improve the high-temperature storage and cycling performance of sodium ion batteries, especially the electrochemical performance under high voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230798A_ABST
    Figure CN119230798A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-ion battery positive electrode material and a preparation method thereof, a positive electrode plate, a sodium-ion battery and power-related equipment, and relates to the technical field of new energy. The shell coating layer of the sodium-ion battery positive electrode material provided by the invention comprises Mn and B, and the Mn element does not generate valence change reaction in the charging and discharging process, so that the effect of maintaining the stability of an electrode structure is achieved, the interface stability of the sodium-ion battery positive electrode material under high voltage is improved, chemical erosion of an electrolyte in the charging process is prevented, and the service life of the sodium-ion battery positive electrode material is prolonged. The transition metal dissolution phenomenon is relieved, and irreversible capacity loss caused by interface structure deterioration in the circulation process is reduced; and the introduction of B tends to occupy the tetrahedral gap position of the Na layer due to the small ion radius in the synthesis process, and a scattering effect can be generated between B < 4 + > and Mn < 3 + > which have the same positive charges, so that Mn < 3 + > can be prevented from being migrated to the tetrahedral gap of Na from the transition metal layer, and the interface stability of the sodium battery positive electrode material under high voltage is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and electrical equipment. Background Art

[0002] Currently, lithium-ion batteries have been widely used in electric vehicles and energy storage due to their high energy density and thermal stability. However, lithium resources are less abundant on Earth and difficult to mine. Therefore, new chemical systems are urgently needed to make up for the shortage of lithium resources. In recent years, sodium-ion batteries have shown great application potential in electrochemical energy storage and medium and low-speed electric vehicles due to their resource and cost advantages.

[0003] The cathode materials of sodium ion batteries can be divided into layered oxides, Prussian blue, polyanions and organic materials according to their composition and structure. Increasing the working voltage is an effective way to increase the energy density of sodium ion batteries. However, when the charging voltage is increased to above 4.0V, the Ni in the cathode material 2+ Will lose electrons and oxidize to Ni 4+ , while the catalytically active Ni 4 + It will react with the electrolyte. This process will not only consume the organic solvent in the electrolyte, but also cause Ni 4+ The reduction of Na forms a layer of inert NiO on the positive electrode surface, reducing + transmission and increase the impedance of the battery, thereby affecting the electrochemical performance of sodium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and electrical equipment, in order to solve the problem that the existing sodium ion battery positive electrode material will reduce the Na by increasing the working voltage. + transmission and increase the battery impedance problem.

[0005] To achieve the above objectives, the present application provides a sodium ion battery positive electrode material, comprising a core and a shell covering the core, wherein the chemical formula of the core is Na a Ni x Fe y Mn Z M1 (1-x-y-z) O2, wherein 0.9≤a≤1.05, 0<x≤1.0, 0≤y≤1.0, 0≤z≤1.0, 0<1-xzy<1.0, M1 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, Sr;

[0006] The chemical formula of the shell is NaM2k B r Mn s O2, wherein 0<r<1, 0≤k<1-rs, and M2 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, and W.

[0007] In some embodiments, the coating amount of the manganese source in the shell is 0.3%-3.5% of the mass of the core.

[0008] In some embodiments, based on the mass of the core, the coating amount of the boron source in the shell is 300-4000 ppm.

[0009] In some embodiments, the coating amount of the M2 source in the shell is 300-10000 ppm based on the mass of the core.

[0010] In some embodiments, at least one of the following conditions is met:

[0011] A. The positive electrode material of the sodium ion battery is a single crystal particle;

[0012] B. The D50 of the sodium ion battery positive electrode material is 4.5-8.3 μm;

[0013] C. The specific surface area of ​​the sodium ion battery positive electrode material is 0.25-0.7m 2 / g;

[0014] D. The tap density of the sodium ion battery positive electrode material is 2.1-3.2 g / cm 3 ;

[0015] E. The thickness of the shell is 1.2-6 nm;

[0016] F. The B element in the shell is distributed in the area of ​​0.2-2.0 nm on the surface.

[0017] The present application also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising:

[0018] The positive electrode material identical to the core is mixed with a manganese source and a boron source, and calcined to obtain the positive electrode material for a sodium ion battery.

[0019] In some embodiments, at least one of the following conditions is met:

[0020] A. The particle size of the manganese source is 30-200 nm;

[0021] B. the manganese source is selected from any one of MnO and (CH3COO)2Mn;

[0022] C. The particle size of the boron source is 30-200nm;

[0023] D. the boron source is selected from any one of H3BO3 and B2O3;

[0024] E. The calcination temperature is 300-750°C;

[0025] F. The calcination time is 5-10h;

[0026] G. The mixing further comprises adding an M2 source, wherein the particle size of the M2 source is 30-200 nm.

[0027] The present application also provides a positive electrode plate, comprising the above-mentioned sodium ion battery positive electrode material.

[0028] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode plate.

[0029] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0030] Compared with the prior art, the beneficial effects of this application include:

[0031] The shell coating layer of the sodium ion battery positive electrode material provided in the present application includes Mn and B. The Mn element does not undergo a valence change reaction during the charge and discharge process, which plays a role in maintaining the stability of the electrode structure, thereby improving the interface stability of the sodium positive electrode material under high voltage, preventing chemical erosion of the electrolyte during the charging process, reducing the dissolution of transition metals, and reducing the irreversible capacity loss caused by the deterioration of the interface structure during the cycle. In addition, the valence state of the Mn element in the positive electrode material is usually a mixed mode of +3 and +4, in which Mn 4+ The proportion is relatively high, Mn 3+ The proportion is relatively low, but due to Mn 3+ The crystal field stabilization energy in the transition metal layer is smaller than that of Mn 4+ , tends to migrate from the octahedral coordination environment of the transition metal layer to the tetrahedral interstitial position of the Na layer, which will lead to oxygen vacancies in the transition metal layer and deteriorate the stability of the structure. The introduction of non-metallic element B tends to occupy the tetrahedral interstitial position of the Na layer during the synthesis process due to its small ionic radius. 4+ With Mn 3 + There will be a scattering effect between them, which will prevent Mn 3+ Migration from the transition metal layer to the tetrahedral gap of Na further improves the interfacial stability of sodium battery cathode materials under high voltage.

[0032] The coating design uses the chemically stable Mn element to suppress the occurrence of interface side reactions, and uses the light element B to prevent trace Mn from 3+The interlayer migration of multiple elements is utilized, and the synergistic effect of multiple elements is used to greatly improve the electrochemical performance of sodium-ion batteries, especially the high-temperature storage performance and cycle performance.

[0033] The positive electrode plate, sodium ion battery and electrical equipment provided in the present application have good energy density and cycle life due to the use of the sodium ion battery positive electrode material of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0035] Figure 1 This is a schematic diagram of the structure of the positive electrode material of the sodium ion battery of the present application;

[0036] Figure 2 It is the cycle capacity retention rate of the sodium ion battery positive electrode material of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0037] As used herein:

[0038] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0039] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0040] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0041] In these examples, parts and percentages are by mass unless otherwise indicated.

[0042] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0043] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0044] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0045] This application provides a sodium ion battery positive electrode material, please refer to Figure 1 , comprising a core and a shell covering the core, wherein the chemical formula of the core is Na a Ni x Fe y Mn Z M1 (1-x-y-z) O2, wherein 0.9≤a≤1.05, 0<x≤1.0, 0≤y≤1.0, 0≤z≤1.0, 0<1-xzy<1.0, M1 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, Sr;

[0046] The chemical formula of the shell is NaM2 k B r Mn s O2, wherein 0<r<1, 0≤k<1-rs, and M2 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, and W.

[0047] The shell coating layer of the sodium ion battery positive electrode material provided in the present application includes Mn and B. The Mn element does not undergo a valence change reaction during the charge and discharge process, which plays a role in maintaining the stability of the electrode structure, thereby improving the interface stability of the sodium positive electrode material under high voltage, preventing chemical erosion of the electrolyte during the charging process, reducing the dissolution of transition metals, and reducing the irreversible capacity loss caused by the deterioration of the interface structure during the cycle. In addition, the valence state of the Mn element in the positive electrode material is usually a mixed mode of +3 and +4, in which Mn 4+ The proportion is relatively high, Mn 3+ The proportion is relatively low, but due to Mn 3+ The crystal field stabilization energy in the transition metal layer is smaller than that of Mn 4+ , tends to migrate from the octahedral coordination environment of the transition metal layer to the tetrahedral interstitial position of the Na layer, which will lead to oxygen vacancies in the transition metal layer and deteriorate the stability of the structure. The introduction of non-metallic element B tends to occupy the tetrahedral interstitial position of the Na layer during the synthesis process due to its small ionic radius. 4+ With Mn 3 + There will be a scattering effect between them, which will prevent Mn 3+ Migration from the transition metal layer to the tetrahedral gap of Na further improves the interfacial stability of sodium battery cathode materials under high voltage.

[0048] This coating design utilizes the chemically highly stable Mn element to inhibit the occurrence of interfacial side reactions, and uses the lightweight element B to prevent the interlayer migration of trace Mn3+. The synergistic effect of multiple elements is used to greatly improve the electrochemical performance of sodium-ion batteries, especially the high-temperature storage performance and cycle performance.

[0049] In some embodiments, the coating amount of the manganese source in the shell is 0.3%-3.5% of the mass of the core, for example, it can be 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, 1.2%, 1.5%, 1.9%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.3%, 3.5% or any value between 0.3% and 3.5%.

[0050] In some embodiments, based on the mass of the inner core, the coating amount of the boron source in the outer shell is 300-4000ppm, for example, it can be 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1500ppm, 1800ppm, 2000ppm, 2200ppm, 2500ppm, 2800ppm, 3000ppm, 3200ppm, 3500ppm, 3700ppm, 4000ppm or any value between 300-4000ppm.

[0051] In some embodiments, the B element in the shell is distributed in the region of 0.2-2.0 nm from the surface.

[0052] In some embodiments, based on the mass of the inner core, the coating amount of the M2 source in the outer shell is 300-10000ppm, for example, it can be 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1500ppm, 1800ppm, 2000ppm, 2200ppm, 2500ppm, 2800ppm, 3000ppm, 3200ppm, 3500ppm, 3700ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm or any value between 300-10000ppm.

[0053] In some embodiments, the sodium ion battery positive electrode material is a single crystal particle; D50 is 4.5-8.3 μm, for example, it can be 4.5 μm, 4.7 μm, 5.0 μm, 5.5 μm, 5.7 μm, 6.0 μm, 6.3 μm, 6.5 μm6.8 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.3 μm or any value between 4.5-8.3 μm.

[0054] In some embodiments, the specific surface area of ​​the sodium ion battery positive electrode material is 0.25-0.7 m 2 / g, for example, 0.25m 2 / g, 0.3m 2 / g, 0.35m 2 / g, 0.4m 2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g or 0.25-0.7m 2 Any value between / g.

[0055] In some embodiments, the tap density of the sodium ion battery positive electrode material is 2.1-3.2 g / cm 3 , for example, it can be 2.1 g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.7g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 or 2.1-3.2g / cm 3 Any value in between.

[0056] In some embodiments, the shell has a thickness of 1.2-6 nm, for example, 1.2 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, or any value between 1.2-6 nm.

[0057] The present application also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising:

[0058] The positive electrode material identical to the core is mixed with a manganese source and a boron source, and calcined to obtain the positive electrode material for a sodium ion battery.

[0059] In some embodiments, the particle size of the manganese source is 30-200 nm, for example, it can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 30-200 nm.

[0060] In some embodiments, the manganese source is selected from any one of MnO and (CH3COO)2Mn.

[0061] In some embodiments, the particle size of the boron source is 30-200 nm, for example, it can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 30-200 nm.

[0062] In some embodiments, the boron source is selected from any one of H3BO3 and B2O3.

[0063] In some embodiments, the calcination temperature is 300-750°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or any value between 300-750°C.

[0064] In some embodiments, the calcination time is 5-10 hours.

[0065] In some embodiments, the mixing also includes adding an M2 source, the particle size of the M2 source is 30-200nm, for example, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or any value between 30-200nm.

[0066] The present application also provides a positive electrode plate, comprising the above-mentioned sodium ion battery positive electrode material.

[0067] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode plate.

[0068] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0069] The positive electrode plate, sodium ion battery and electrical equipment provided in the present application have good energy density and cycle life due to the use of the sodium ion battery positive electrode material of the present application.

[0070] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0071] Example 1

[0072] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0073] (1) Nickel sulfate / manganese sulfate / iron sulfate solution and aluminum sulfate were uniformly mixed in a ratio of Ni:Fe:Mn:Al=40:20:35:5 to obtain a metal salt solution with a total metal ion concentration of 3.1 mol / L. 2 mol / L ammonia water and sodium hydroxide solution were added to the metal salt solution for neutralization. A precipitate was obtained by coprecipitation. The obtained precipitate was filtered and washed, and dried at 200°C for 5 h to obtain a hydroxide precursor Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2.

[0074] (2) The hydroxide precursor Ni obtained in step (1) 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly and sintered in stages in a sintering furnace: first, the temperature was raised to 400°C at a heating rate of 3°C / min for 8h of pre-sintering in an air atmosphere, and then the temperature was raised to 940°C at a heating rate of 3°C / min for 16h in an air atmosphere. After sintering, the cathode material Na was cooled in the furnace and obtained. 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.

[0075] (3) Obtain material Na in step (2) 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 0.5% by mass of MnO with a particle size of 50 nm and 500 ppm of H3BO3 with a particle size of 100 nm were added to O2, and after being mixed evenly, they were calcined at 650° C. for 6 h to finally obtain the sodium ion battery positive electrode material of Example 1.

[0076] Example 2

[0077] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0078] (1) A nickel sulfate / manganese sulfate / iron sulfate solution and titanium sulfate were mixed in a ratio of Ni:Fe:Mn:Ti=30:20:45:5 to obtain a metal salt solution with a total metal ion concentration of 1.1 mol / L. 2 mol / L ammonia water and sodium hydroxide solution were added to the metal salt solution for neutralization. A precipitate was obtained by coprecipitation. The obtained precipitate was filtered and washed, and dried at 200°C for 5 hours to obtain a hydroxide precursor Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05 (OH)2.

[0079] (2) The hydroxide precursor Ni obtained in step (1) 0.3 Fe 0.2 Mn 0.45 Ti 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly and sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h of pre-sintering in an air atmosphere, and then the temperature was increased to 950°C at a heating rate of 3°C / min for 16h in an air atmosphere. After sintering, the cathode material Na was cooled in the furnace and obtained. 1.01 Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.

[0080] (3) Obtain material Na in step (2) 1.01 Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05 In O2, 1% by mass of MnO with a particle size of 50nm, 650ppm of H3BO3 with a particle size of 100nm and 1000ppm of Al2O3 with a particle size of 100nm are added, and after mixing evenly, calcined at 580°C for 6h to finally obtain the sodium ion battery positive electrode material of Example 2.

[0081] Example 3

[0082] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0083] (1) Nickel sulfate / manganese sulfate / ferric sulfate solution / aluminum sulfate and copper sulfate solution were uniformly mixed in a ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a metal salt solution with a total metal ion concentration of 3.2 mol / L. 2 mol / L ammonia water and sodium hydroxide solution were added to the metal salt solution for neutralization. A precipitate was obtained by coprecipitation. The obtained precipitate was filtered and washed, and dried at 200° C. for 5 h to obtain a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2.

[0084] (2) As in Example 1, the positive electrode material Na 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2.

[0085] (3) The sodium ion battery positive electrode material of Example 3 is obtained in the same manner as in Example 1.

[0086] Example 4

[0087] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0088] (1) Nickel sulfate / manganese sulfate / ferric sulfate solution / aluminum sulfate and copper sulfate solution were uniformly mixed in a ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a metal salt solution with a total metal ion concentration of 3.9 mol / L. 2 mol / L ammonia water and sodium hydroxide solution were added to the metal salt solution for neutralization. A precipitate was obtained by coprecipitation. The obtained precipitate was filtered and washed, and dried at 200° C. for 5 h to obtain a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2.

[0089] (2) As in Example 1, the positive electrode material Na 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2.

[0090] (3) Obtain material Na in step (2) 1.01 Ni 0.35 Fe0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, add 2% by mass of (CH3COO)2Mn with a particle size of 50nm and 1000ppm of H3BO3 with a particle size of 100nm, mix well and calcine at 710℃ for 8h to finally obtain the sodium ion battery positive electrode material of Example 4.

[0091] Example 5

[0092] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0093] (1) As in Example 4, a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2.

[0094] (2) As in Example 4, the positive electrode material Na 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2.

[0095] (3) Obtain material Na in step (2) 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, add 2.5% by mass of (CH3COO)2Mn with a particle size of 50nm, 800ppm of H3BO3 with a particle size of 100nm and 500ppm of TiO2 with a particle size of 100nm, mix well and calcine at 700℃ for 8h to finally obtain the sodium ion battery positive electrode material of Example 5.

[0096] Example 6

[0097] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0098] (1) Nickel sulfate / manganese sulfate / iron sulfate solution and zinc sulfate solution / titanium sulfate were uniformly mixed in a ratio of Ni:Fe:Mn:Zn:Ti=35:20:35:5:5 to obtain a metal salt solution with a total metal ion concentration of 4.3 mol / L. 2 mol / L ammonia water and sodium hydroxide solution were added to the metal salt solution for neutralization. A precipitate was obtained by coprecipitation. The obtained precipitate was filtered and washed, and dried at 200° C. for 5 h to obtain a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.05 Ti 0.05 (OH)2.

[0099] (2) As in Example 1, obtain the positive electrode material Na 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.05 Ti 0.05 O2.

[0100] (3) The positive electrode material Na obtained in step (2) 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.05 Ti 0.05 1.5% by mass of MnO with a particle size of 50 nm and 465 ppm of B2O3 with a particle size of 100 nm were added to O2, and after mixing evenly, calcined at 690° C. for 8 h, finally obtaining the sodium ion battery positive electrode material of Example 6.

[0101] Example 7

[0102] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0103] (1) As in Example 6, a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.05 Ti 0.05 (OH)2.

[0104] (2) The only difference from Example 6 is that the sintering temperature in step (2) is increased to 980°C, and other parameters remain unchanged to obtain the positive electrode material Na 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.05 Ti 0.05 O2.

[0105] (3) The same as Example 6, finally obtaining the sodium ion battery positive electrode material of Example 7.

[0106] Example 8

[0107] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0108] (1) As in Example 1, a hydroxide precursor Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2.

[0109] (2) The only difference from Example 1 is that the molar ratio of metal cations to Na ions in step (2) is changed to 1:0.98, and other parameters remain unchanged to obtain the positive electrode material Na 0.98 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 O2.

[0110] (3) The same as Example 1, finally obtaining the sodium ion battery positive electrode material of Example 8.

[0111] Comparative Example 1

[0112] Comparative Example 1 provides a sodium ion battery positive electrode material, which is the positive electrode material Na obtained in step (2) of Example 1. 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 O2.

[0113] Comparative Example 2

[0114] Comparative Example 2 provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0115] Steps (1) and (2) are the same as in Example 1.

[0116] (3) In Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1000 ppm of nano-Al2O3 particles and 1000 ppm of ZrO2 were added to the O2 material, mixed evenly, and sintered at 560° C. for 6 h to obtain the sodium ion battery positive electrode material of Comparative Example 2.

[0117] Comparative Example 3

[0118] Comparative Example 3 provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0119] Steps (1) and (2) are the same as in Example 1.

[0120] (3) In Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1000 ppm of nano-Al2O3 particles and 500 ppm of MgO were added to the O2 material, mixed evenly, and sintered at 550° C. for 6 h to obtain the sodium ion battery positive electrode material of Comparative Example 3.

[0121] Comparative Example 4

[0122] Comparative Example 4 provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0123] Steps (1) and (2) are the same as in Example 1.

[0124] (3) In Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1.0%wt of nano MnO particles were added to the O2 material, the mixture was evenly mixed and then sintered at 650°C for 8h to obtain the sodium ion battery positive electrode material of Comparative Example 4.

[0125] Comparative Example 5

[0126] Comparative Example 5 provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0127] Steps (1) and (2) are the same as in Example 1.

[0128] (3) In Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1000 ppm of nano H3BO3 was added to the O2 material, mixed evenly, and then sintered at 500° C. for 6 h to obtain the sodium ion battery positive electrode material of Comparative Example 5.

[0129] Comparative Example 6

[0130] The difference from Example 2 is that in step (2) the material Na is obtained. 1.01 Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05O2, add 1% by mass of MnO with a particle size of 50nm and 1000ppm of Al2O3 with a particle size of 100nm, mix well and calcine at 580°C for 6h, and finally obtain the sodium ion battery positive electrode material of Comparative Example 6.

[0131] The sodium ion battery positive electrode materials prepared in the above embodiments and comparative examples are respectively mixed according to the positive electrode sheet formula: the mass ratio of positive electrode active material, conductive carbon black, conductive carbon tube, polyvinylidene fluoride and N-methylpyrrolidone is 96.5:1:0.5:2:40, and the mixture is stirred at 500rpm for 4h to obtain sodium positive electrode material slurry, and the prepared positive electrode slurry is evenly coated on aluminum foil with a scraper, placed in a blast drying oven, and dried at 120°C for 20min. Finally, the dried electrode sheet is rolled and cut to make a positive electrode sheet. The obtained positive electrode sheet and the negative electrode and diaphragm prepared by hard carbon are assembled into a 1.3Ah soft-pack battery cell after winding, packaging, injection and other processes. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are evenly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coated film is selected as the diaphragm.

[0132] Battery performance test:

[0133] Constant capacity test: The 1.3Ah soft-pack battery cell prepared by the above method was charged for the first time in the voltage range of 1.5-4.0V with a rate of 0.2C and a cut-off current of 0.02C. It was charged to 4.0V with constant current and constant voltage, and then discharged at 0.33C until the cut-off value was 1.5V. The initial charge and discharge capacity was tested.

[0134] pH paper strip method to test pH: by immersing the reagent in the liquid to be tested, and then reading the pH value according to the color change of the paper strip coated with the reagent.

[0135] Cyclic performance test: At 25°C and in the range of 1.5-4.0V, charge at a rate of 0.5C with a cut-off current of 0.05C, then discharge at a rate of 1C to the lower limit voltage, and cycle 2000 times.

[0136] The electrochemical properties of the sodium ion battery positive electrode materials of each embodiment and comparative example are shown in Table 1. The cycle capacity retention rates of the sodium ion battery positive electrode materials of embodiments 1-3 and comparative examples 1-2 are shown in Table 1. Figure 2 shown.

[0137] Table 1 Electrochemical properties of sodium ion battery positive electrode materials of various embodiments and comparative examples

[0138]

[0139]

[0140] From Table 1 and Figure 2 It can be seen that compared with comparative examples 1-5, the sodium battery positive electrode materials coated with Mn and B obtained in the present application by adjusting the types and contents of the coating elements in Examples 1 to 8 have higher capacity and cycle capacity retention rate than the positive electrode materials without Mn and B coating in Comparative Examples 1-5.

[0141] According to Comparative Examples 1 and 4, the coating layer in Comparative Example 4 contains only Mn element. Since Mn will deteriorate the battery kinetic performance, resulting in low gram capacity, its electrochemical performance is lower than that of Comparative Example 1 without a coating layer. After adding element B to the coating layer, the kinetic performance will be significantly improved, and both gram capacity and cycle performance will be improved.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0143] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A sodium ion battery positive electrode material, characterized in that: It comprises a core and a shell covering the core, wherein the chemical formula of the core is Na a Ni x Fe y Mn Z M1 (1-x-y-z) O2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xzy<1.0, M1 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, Sr; The chemical formula of the shell is NaM2 k B r Mn s O2, wherein 0<r<1, 0≤k<1-rs, and M2 is selected from one or more of Al, Mg, Ti, Zr, Y, La, Ca, and W.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The coating amount of the manganese source in the shell is 0.3%-3.5% of the mass of the core.

3. The sodium ion battery positive electrode material according to claim 1, characterized in that Based on the mass of the inner core, the coating amount of the boron source in the outer shell is 300-4000 ppm.

4. The sodium ion battery positive electrode material according to claim 1, characterized in that Based on the mass of the inner core, the coating amount of the M2 source in the outer shell is 300-10000 ppm.

5. The sodium ion battery positive electrode material according to claim 1, characterized in that At least one of the following conditions is met: A. The positive electrode material of the sodium ion battery is a single crystal particle; B. The D50 of the sodium ion battery positive electrode material is 4.5-8.3 μm; C. The specific surface area of ​​the sodium ion battery positive electrode material is 0.25-0.7m 2 / g; D. The tap density of the sodium ion battery positive electrode material is 2.1-3.2 g / cm 3 ; E. The thickness of the shell is 1.2-6 nm; F. The B element in the shell is distributed in the area of ​​0.2-2.0 nm on the surface.

6. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 5, characterized in that: include: The positive electrode material identical to the core is mixed with a manganese source and a boron source, and calcined to obtain the positive electrode material for a sodium ion battery.

7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: At least one of the following conditions is met: A. The particle size of the manganese source is 30-200 nm; B. the manganese source is selected from any one of MnO and (CH3COO)2Mn; C. The particle size of the boron source is 30-200nm; D. the boron source is selected from any one of H3BO3 and B2O3; E. The calcination temperature is 300-750°C; F. The calcination time is 5-10h; G. The mixing further comprises adding an M2 source, wherein the particle size of the M2 source is 30-200 nm.

8. A positive electrode sheet, characterized in that: The sodium ion battery positive electrode material comprises any one of claims 1 to 5.

9. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 8.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.